Aladdin - Stuart, Marie (London : Lady bird Ltd)
A kind-hearted street urchin and a power-hungry Grand Vizier vie for a magic lamp that has the power to make their deepest wishes come true. Aladdin is a poor street urchin who spends his time stealing food from the marketplace in the city of Agrabah. His adventures begin when he meets a young girl who happens to be Princess Jasmine, whose wacky, estranged father is forcing her to get married. Aladdin's luck suddenly changes when he retrieves a magical lamp from the Cave of Wonders. What he unwittingly gets is a fun-loving genie who only wishes to have his freedom. Little do they know that the Sultan's sinister advisor Jafar has his own plans for both Aladdin and the lamp. $1 (BBlazer346 When street rat Aladdin frees a genie from a lamp, he finds his wishes granted. However, he soon finds that the evil Jafar has other plans for the lamp--and for Princess Jasmine. Can Aladdin save Princess Jasmine and his love for her after she sees that he isn't quite what he appears to be? $1 (BJwelch5742 Aladdin is a poor yet carefree street urchin in an Arabian city. One day he meets Princess Jasmine, the daughter of the Sultan of the land, and falls madly in love. However, the evil Jafar, the Sultan's advisor, imprisons Aladdin and manipulates him into working for him. Unknown to Aladdin, he is the only one who can enter and unlock the treasures of a secret cave, including a magical lamp. Aladdin finds the lamp and releases the genie trapped within. The genie offers to grant him three wishes. Meanwhile, Jafar wants the lamp and the Princess has to be married within three days. Many adventures follow. $1 (Bgrantss Aladdin is a street urchin who lives in a large, busy town long ago with his faithful monkey friend Abu. When Princess Jasmine gets tired of being forced to remain in the palace that overlooks the city, she sneaks out to the marketplace, where she accidentally meets Aladdin. Under the orders of the evil Jafar (the sultan's advisor), Aladdin is thrown in jail and becomes caught up in Jafar's plot to rule the land with the aid of a mysterious lamp. Legend has it that only a person who is a "diamond in the rough" can retrieve the lamp from the Cave of Wonders. Aladdin might fit that description, but that's not enough to marry the princess, who must (by law) marry a prince.s
English fiction book
Keywords: English - Fiction book